The human rab genes encode a family of GTP - binding proteins related to yeast YPT1 and SEC4 products involved in secretion - Zahraoui, A.; Touchot, N.; Chardin, P.; Tavitiam, A. (1995)
Seven cDNA clones corresponding to the rabl, rab2, rab3A, rab3B, rab4, rab5, and rab5 genes were isolated from a human pheochromocytoma cDNA library. They encode 23-25 kDa polyeptides which share =30-50 percent homology and belong to the ras superfamily. The rab1, rab2, rab3A, and rab4 proteins are the human counterparts of the rat rab gene products that we have previously characterized. Comparison of the seven human rab proteins with the yeast YPT1 (YPT1p) and SEC4 (SEC4p) proteins reveals highly significant sequence similarities. H-rablp shows 75 percent amino acid identity with YPT1p and may be therefore considered as its human counterpart. The other proteins share =40 percent homology with YPT1p and SEC4p. The homology (=30 percent) between these rab proteins and p21 ras is restricted to the four conserved domains involved in the GTP/GDP binding. Human rab proteins were produced in Escherichia coli. Large amounts of rab proteins in soluble form can be extracted and purified without the use of detergents. All six proteins bind GTP and exhibit GTPase activities. A possible involvement of the rab proteins in secretion is discussed.